2021
DOI: 10.3390/antiox11010103
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of an Oxidative Stress Model with Sodium Iodate Revealed Protective Effect of NF-κB Inhibition and Sex-Specific Difference in Susceptibility of the Retinal Pigment Epithelium

Abstract: Oxidative stress of the retinal pigment epithelium (RPE) is a major risk factor for age-related macular degeneration (AMD). As a dry AMD model via oxidative stress, sodium iodate (NaIO3), which is primarily toxic to the RPE, has often been used at a high dose to cause RPE death for studying photoreceptor degeneration. Thus, characterization of RPE damage by a low dose of NaIO3 is still limited. To quantify RPE damage caused by NaIO3 in mice, we recently developed a morphometric method using RPE flat-mounts. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 77 publications
3
10
0
Order By: Relevance
“…Therefore, the earliest time point to analyze RPE flat-mounts with ease and consistency was day 7, which we chose as the universal time point for analyzing the extent of RPE damage throughout this study. During these preliminary studies, we also observed that RPE damage by NaIO 3 was not evenly distributed as previously noted ( Xia et al, 2011 ; Ma et al, 2020 ; Upadhyay et al, 2020 ; Wolk et al, 2020 ; Yang et al, 2021 ; Zhang et al, 2021 ). Although RPE in the periphery was well preserved, RPE in the center (posterior) around the optic nerve head was severely damaged, either degenerated or completely lost, compared with control mice with the vehicle ( Fig 1a and b ).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Therefore, the earliest time point to analyze RPE flat-mounts with ease and consistency was day 7, which we chose as the universal time point for analyzing the extent of RPE damage throughout this study. During these preliminary studies, we also observed that RPE damage by NaIO 3 was not evenly distributed as previously noted ( Xia et al, 2011 ; Ma et al, 2020 ; Upadhyay et al, 2020 ; Wolk et al, 2020 ; Yang et al, 2021 ; Zhang et al, 2021 ). Although RPE in the periphery was well preserved, RPE in the center (posterior) around the optic nerve head was severely damaged, either degenerated or completely lost, compared with control mice with the vehicle ( Fig 1a and b ).…”
Section: Resultssupporting
confidence: 83%
“…Using RPE flat-mounts with phalloidin staining that outlines the RPE cell shape, Xia et al reported that NaIO 3 injection in mice produced three regions with distinct RPE morphologies: normal cobblestone-like RPE (periphery), atrophic damaged RPE (center), and irregular elongated cells between the two regions (transitional zone) ( Xia et al, 2011 ). Recently, several others and we also observed similar RPE morphologies induced by NaIO 3 in mice ( Ma et al, 2020 ; Upadhyay et al, 2020 ; Wolk et al, 2020 ; Yang et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The decrease of these amino acids may predispose the female RPE to oxidative damage. Consistently, Female mice show more severe RPE damage and reduced retinal thickness under oxidative damage induced by sodium iodate 63,64 . RPE mitochondria prefer to oxidize succinate from the retina to produce malate and fumarate for the retina [65][66][67] .…”
Section: Tissue-specific Sex-different Metabolitesmentioning
confidence: 63%